Proposition of a protocol to evaluate upper-extremity functional deficits and compensation mechanisms: application to elbow contracture - Fradet, Laetitia; Liefhold, Beate; Rettig, Oliver; Bruckner, Thomas; Akbar, Michael; Wolf, Sebastian Immanuel (Journal of orthopaedic science, 2015)
Objective - Instrumented gait analysis is widely acceptedas an objective assessment of lower-extremity function. Conversely, upper-extremity function suffers from lack of objective evaluation. The present paper aims at proposing a protocol to be used to clinically and objectively evaluate upper-extremity function whatever the pathological joint. Secondly, it aims at better understanding the consequences on upper-extremity function and the compensation mechanisms induced by elbow contracture. Elbow contracture was simulated in this study by using a brace. - Design - Twelve healthy subjects followed an instrumented3D movement analysis while performing 11 daily life movements. The movements were performed with 3 differentelbow contracture conditions, simulated by wearing an adjustable elbow brace. - Results - The proposed protocol was successful in creatinga wide range of motion at all the upper-extremity joints. The activity-related range of motion and the mean range of motion computed on the whole set of daily life movements were effective in evaluating the severity of elbow contracture. The lack of elbow flexion was compensated by trunk flexion, hand flexion and radial deviation, and combined movement of shoulder flexion, abduction, and humeral internal rotation. Deficit in elbow extension was mainly compensated by the use of trunk flexion. - Conclusions - A protocol could be proposed for the objectiveevaluation of upper-extremity function. Its application to elbow contracture suggests that loss of elbow flexion affects more movements than loss of elbow extension.
Gesehen am 10.06.2020